Novel SCN5A Frameshift Mutation in Brugada Syndrome Associated With Complex Arrhythmic Phenotype - Micaglio, Emanuele; Monasky, Michelle M.; Ciconte, Giuseppe; Vicedomini, Gabriele; Conti, Manuel; Mecarocci, Valerio; Giannelli, Luigi; Giordano, Federica; Pollina, Alberto; Saviano, Massimo; Pozzi, Paolo R.; Di Resta, Chiara; et al. (Frontiers in Genetics, 2019)
In this case report, we characterize a novel inherited frameshift mutation c.4700_4701del (p.Phe1567Cysfs*221) in a single copy of the SCN5A gene and its association with Brugada syndrome (BrS). The proband experienced a life-threatening ventricular arrhythmia successfully treated with DC-shock and he also suffered from supraventricular tachycardia. Ajmaline test confirmed the BrS diagnosis. No other mutation nor low frequency variants in the other 23 analyzed genes were detected. The same mutation was found in the father and sister, who were both diagnosed with BrS. We hypothesize that this mutation could be responsible for BrS and potentially linked to supraventricular tachycardias. Further studies are needed to confirm this observation and to assess the clinical relevance of this mutation, in terms of risk-stratification.